The Importance of Using Logo Design as a Brand Image in Marketing MSME Products Using Digital Technology in Kelambir V Village - Yusup, Mohammad (International Conference on Sciences Development and Technology, 2023)
The use of logo design as a key element in branding strategy plays a central role in enhancing the marketing of SME products in the digital era, especially in Kelambir V Village. This research explores the importance of implementing logo design to shape a positive brand image and expand market reach for SME practitioners. Through training, workshops, and the implementation of digital technology, this community engagement program aims to enhance the understanding of SME practitioners regarding the role of logo design in creating visual appeal and strengthening brand identity. Additionally, through collaboration with academic institutions and the village government, the project also aims to improve digital technology capacity at the local level. With a focus on Kelambir V Village, it is expected that the implementation of logo design and digital technology will have a significant positive impact on the marketing of SME products, enhance their competitiveness, and stimulate economic growth at the village level. The results of this engagement can serve as a model for the strategic use of logo design and digital technology in developing SME businesses in a rural context.